Development Of Lung Adenocarcinoma With Epidermal Growth Factor Receptor Mutation In Patients With Breast Cancer History: Case Report (2016)
Mutation of exons 19 and 21 encoding for Epidermal Growth Factor Receptor (EGFR) tyrosine Kinase domain, is found in 15-20% of lung adenocarcinomas (NSCLC) and in 0.8-1.4% of breast carcinomas (BC) with negative hormonal receptors. Radiotherapy is considered an indiscriminate activation factor of EGFR. Objetive: To report 2 cases of BC treated with chemo radiotherapy that later developed NSCLC with EGFR mutation